Induction of Migration and Collagen Synthesis in Human Gingival Fibroblasts Using Periodontal Ligament Stem Cell Conditioned Medium - Banlue, Akkapol; Kaewmuangmoon, Jirattikarn; Janebodin, Kajohnkiart; Tansriratanawong, Kallapat (European Journal of Dentistry, 2023)
Objective This study aimed to examine the effect of periodontal ligament stem cell conditioned medium (PDLSC-CM) on human gingival fibroblast (HGF) migration and collagen synthesis.Materials and Methods To assess cell viability, we extracted PDLSC-CM, and the total derived protein concentration was adjusted to 12.5 to 200 µg/mL, followed by treatment with HGFs. The viability of HGFs was observed for 24 hours using the MTT assay. Cell migration was monitored for 24 to 48 hours by wound healing and Boyden chamber assays. Collagen synthesis from HGFs was examined by picrosirius red dye and real-time polymerase chain reaction (PCR) to measure collagen type I and III gene expression for 7 to 10 days. A comparison among the groups was assessed using a one-way analysis of variance (ANOVA) and Bonferroni post hoc test, with the exception of the cell viability assay, which was subjected to Welch's test and Dunnett's T3 post hoc test.Results HGF viability was significantly enhanced by 12.5, 25, and 50 µg/mL PDLSC-CM. The HGFs treated with 50 µg/mL PDLSC-CM promoted cell migration as shown by wound healing and Boyden chamber assays. At this concentration, collagen synthesis increased at 10 days. Collagen type I gene expression increased by 1.6-fold (p < 0.001) and 4.96-fold (p < 0.001) at 7 and 10 days, respectively. Collagen type III gene expression showed an increase of 1.76-fold (p < 0.001) and 6.67-fold (p < 0.001) at the same time points.Conclusion Our study suggested that a low concentration of PDLSC-CM at 50 µg/mL has given an amelioration of HGFs providing for periodontal wound healing and periodontal regeneration, particularly migration and collagen synthesis.
Keywords: cell migration; collagen synthesis; culture media; conditioned; fibroblasts; periodontal ligament; stem cells